Molecular diagnosis of antibiotic resistance - McHugh, Tim (Henry Stewart Talks, 2009)
Diagnosis and monitoring are different disciplines, Molecular tools detect genotypic variation, Role for molecular tools in clinical practice, Examples are penicillin binding proteins in Streptococcus pneumoniae, drug resistant Mycobacterium tuberculosis and MRSA
Archived at 2016/06/21